Analysis of Hygiene Sanitation of Cage Workers and Density of Flies in Laying Hens in Nagari Tigo Jangko, Tanahdatar Regency, West Sumatra Province in 2022: Analisis Hygiene Sanitasi Pekerja Kandang Dan Kepadatan Lalat Pada Kandang Ayam Petelur Di Nagari Tigo Jangko Kabupaten Tanahdatar Provinsi Sumatera Barat Tahun 2022 - Nurul Anisyah Pratiwi; Sri Wardani; Benny Yulianto (Badnur Medisa Group, 2022)
On chicken coops in Nagari Tigo Jangko Village, Tanah Datar Regency, there were 7 chicken coops. Among the 7 chicken coops, researchers found a chicken coop with a total of 8000 chickens, where the hygiene of the workers and the sanitation of the cage were problematic, causing a lot of flies and affecting the surrounding community.. The purpose of this study was to analyze hygiene and density levels of laying hens cage flies in Nagari Tigo Jangko, Tanah Datar Regency. The method used was qualitative with a case study approach this research was conducted in a layer chicken coop in Nagari Tigo Jangko in May 2022 with a total of 5 informants. Data collection tools using observation sheets and fly grill, as well as data processing using triangulation techniques. The results of the study showed that the personal hygiene of the coop workers did not use PPE at all, did not regularly wash their hands with soap due to not wearing protective clothing and the skin hygiene of the workers experienced itching and for sanitation, chicken manure was cleaned once a week, there was no special reservoir for manure. , the distance of the cage is too close, which is 15 meters from the house and the unavailability of a hand washing place at the location of the cage. The result of a very high fly density level is >20. It is recommended to cage owners to provide personal protective equipment and pay more attention to cage sanitation in terms of cleaning the cage such as a place to wash hands with soap and the availability of a holding tank so as not to cause flies and cage workers to care more about personal hygiene and use personal protective equipment when working in the field.